15 days ‘water only fast’: a tough but a challenging personal experience - Vohra, Poonam; Jasuja, K.L. (International Journal of Scientific Reports, 2016)
Hydrotherapy is the use of water in the treatment of diseases. It is an effective method of detoxification. It was formerly called hydropathy. Water comprises from 75% body weight in infants to 55% in elderly and is essential for cellular homeostasis and life. The use of water for therapy has been around for hundreds of years. The theory behind it is that water has many properties that give it the ability to heal:water can store and carry heat and energy. Though water fasting offers the quickest detox and strongest therapeutic effect, it is no doubt the most challenging fast to perform in the first few days.